Academic Generations and Academic Work: Patterns of Attitudes, Behaviors and Research Productivity of Polish Academics after 1989 - Kwiek, Marek (My University, 2015)
This paper focuses on a generational change taking place in the Polish academic profession: a change in behaviors and attitudes between two groups of academics. One was socialized to academia under the communist regime (1945-1989) and the other entered the profession in the post-1989 transition period. Academics of all age groups are beginning to learn how tough the competition for research funding is, but young academics (“academics under 40”), being the target of recent policy initiatives, need to learn faster. Current reforms present a clear preferred image for a new generation of Polish academics: highly motivated, embedded in international research networks, publishing mostly internationally, and heavily involved in the competition for academic recognition and research funding. In the long run, without such a radical approach, any international competition between young Polish academics (with a low research orientation and high teaching hours) and their young Western European colleagues (with a high research orientation and low teaching hours) seems inconceivable, as our data on the average academic productivity clearly demonstrate. The quantitative background of this paper comes from 3,704 returned questionnaires and the qualitative background from 60 semi-structured in-depth interviews. The paper takes a European comparative approach and contrasts Poland with 10 Western European countries (using 17,211 returned questionnaires).
Keywords: academic work; academic generations; junior scholars; research time allocation; research productivity; European academics; Polish academics; European universities; academic under 40; older academics; academic cohorts; academic productivity; index of productivity; measuring productivity; teaching and research; teaching vs. research; working time distribution; research time distribution; Polish universities; academic feudalism; academic collegiality; Polish reforms; higher education reforms; young Polish academics; research role orientation; academic role orientation; CAP data; CAP; EUROAC data; EUROAC